Comparative performance evaluation of basalt fiber–modified hot in-place (HIP) recycling asphalt mixtures: site mixture versus lab mixture - Li, Bo; Zhang, Yu; Xiao, Peng; Wang, Yu; Kang, Aihong; Zhang, Yao (Frontiers in Materials, 2023)
The performance improvement of hot in-place recycling asphalt mixtures has been a hot topic recently due to the widespread application of HIP recycling technology. Based on the maintenance project of the provincial pavement G233 Baoying section, basalt fibers were introduced into HIP recycling mixtures. The effect of basalt fiber on the comprehensive performance of recycled mixtures was investigated using high temperature stability tests, cracking resistance tests, water stability tests, and dynamic modulus tests. Moreover, the performance of site mixtures was comparatively investigated with that of lab-made mixtures to further explore the site mixing effect on the mixture performance. The results showed that the recycled mixtures without basalt fiber presented unqualified cracking resistance even though proper mixture design was performed. The addition of basalt fibers could greatly enhance the rutting resistance, low-temperature cracking resistance, and stripping resistance of HIP recycled mixtures by 105.2%, 102.3%, and 46.9%, respectively. Moreover, the mixing method also had a significant impact on the properties of mixtures. The recycled mixtures produced by the site re-mixing method showed inferior performance compared to that of mixtures produced by the lab mixing method. Specifically, the dynamic stability, low temperature failure strain, and stripping point values reduced by 44.1%, 16.2%, and 11.7%, respectively, indicating that the site re-mixing process was not as effective as the lab mixing process due to the weaker blending and mixing procedures of the site equipment. The results could be beneficial for the utilization of basalt fiber in HIP recycling technology.